Relations between caregiver-report of sleep and executive function problems in children with autism spectrum disorder and attention-deficit/hyperactivity disorder. (November 2019) - Cremone-Caira, Amanda; Buirkle, Julia; Gilbert, Rachel; Nayudu, Nikita; Faja, Susan
Highlights: Many children with ASD have comorbid symptoms of ADHD. Children with ASD and ADHD often have deficits in sleep and executive functioning. Whether sleep and executive functioning predict ADHD symptoms in ASD is unknown. Sleep and executive functioning deficits predicted ADHD symptoms independently. Children with difficulties with working memory were particularly at risk for ADHD. Abstract: Background: Many children with autism spectrum disorder (ASD) experience comorbid symptoms of attention-deficit/hyperactivity disorder (ADHD). Additionally, children with ASD and ADHD often have sleep disturbances and deficits in executive functioning (EF). In typical development, sleep disturbances are causally linked to EF deficits and exacerbate ADHD-like symptoms. Aim: The aim of this study was to determine whether caregiver-report sleep and EF difficulties predict ADHD symptoms in children with ASD. Methods: Caregiver-report of child sleep, EF, and ADHD symptom severity was collected for 101 children with ASD, 7–11 years of age. Hierarchical linear regressions tested the independent and interactive effects of sleep and EF in predicting ADHD symptoms. Results: Children with ASD were more likely to have symptoms of ADHD if they experienced both sleep and EF difficulties. Children with difficulties in working memory were particularly at risk for clinically significant symptoms of ADHD. Notably, however, sleep did not mediate or moderate the relation between working memory and ADHD symptoms in this sample, suggesting that these variables act through independent mechanisms to increase vulnerability for comorbidity. Conclusions: These results have clinical significance as sleep and EF deficits may identify an ASD subgroup that is at increased risk for a comorbid ADHD diagnosis.